2022
DOI: 10.1097/jom.0000000000002635
|View full text |Cite
|
Sign up to set email alerts
|

Working From Home During COVID-19

Abstract: The aim of the study is to investigate whether work-family conflict and/or family-work conflict mediated the relationship between workplace characteristics and general health and job satisfaction in a sample of workers working from home in a recommended/mandatory context due to COVID-19 measures. Methods: Data were collected via online questionnaire as part of the Employees Working from Home study. Analyses in this article used data collected at 2 time points 6 months apart, including 965 complete responses fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 87 publications
1
10
0
Order By: Relevance
“…For men, high physical demands and relatively high WFC were associated with increased levels of low back pain. Mediation of the relationships between work‐related hazards and general health and job satisfaction by WFC has also been found in groups undertaking mandated work from home 27 …”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…For men, high physical demands and relatively high WFC were associated with increased levels of low back pain. Mediation of the relationships between work‐related hazards and general health and job satisfaction by WFC has also been found in groups undertaking mandated work from home 27 …”
Section: Introductionmentioning
confidence: 91%
“…13,14,25,26 Further work has explored whether WFC or FWC act as mediators or moderators of the relationships between workplace hazards and musculoskeletal pain. 15,16,27 Weale et al 15 reported WFC to mediate relationships between a number of work-related hazards (high physical demands, high workload, poor relationships with management, poor safety climate, and a poor physical work environment) and musculoskeletal pain. In a later study, Weale et al 16 found WFC moderated the relationship between workplace hazards and musculoskeletal pain; however, results differed for men and women.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations